Diversity of the medicinal plant in homegarden of local communities in the coastal area of Prigi Bay, Trenggalek, East Java, Indonesia - NIA AGUSTINA; TIMOTHY JEFFREY WALTER HUTAURUK; NUNIK SULISTYANINGRUM; SYARIFUDIN MAHFUDH YUDHANTO; NOR LIZA; LIA KUSUMANINGRUM; SUGIYARTO SUGIYARTO; AHMAD YASA; SURAPON SAENSOUK; DARLINA MD. NAIM; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2022)
Abstract. Agustina N, Hutauruk TJW, Sulistyaningrum N, Yudhanto SM, Liza N, Kusumaningrum L, Sugiyarto, Yasa A, Saensouk S, Naim DMD, Setyawan AD. 2022. Diversity of the medicinal plant in homegarden of local communities in the coastal area of Prigi Bay, Trenggalek, East Java, Indonesia. Biodiversitas 23: 6302-6312. Homegarden is a part of the agroforestry system that is essential in a food security program. It also reflects the social and traditional practices in certain areas that define the composition of plants. One common plant that grows in a homegarden area is herbal medicine. The knowledge about medicinal plants in society is essential to ensure the sustainability of this local wisdom to be passed through the subsequent generations. This research aimed to examine the diversity of medicinal plants planted in homegarden in Tasikmadu, Prigi, and Karanggandu Villages, Watulimo Sub-district, East Java, Indonesia. The research used a field survey of plant inventory and a semi-structured interview to gather ethnobotanical information. A total of 60 respondents were obtained by purposive sampling, with residents with homegardens preferred to be interviewed. The discussion results showed that 32 families of 59 medicinal plant species found in the study areas are consumed for medicinal purposes. Zingiberaceae is referred to as the highest family consumed by the respondents. Leaves and rhizomes are the most commonly utilized part, while decoction is the most popular preparation method. This study revealed that people aged 46-55 have the highest knowledge of medicinal plants. At the same time, women are considered to know more about herbal medicine compared to men.